2020
DOI: 10.3390/jcm9030702
|View full text |Cite
|
Sign up to set email alerts
|

Do Nutritional Factors Interact with Chronic Musculoskeletal Pain? A Systematic Review

Abstract: Dietary patterns may play an important role in musculoskeletal well-being. However, the link between dietary patterns, the components of patients’ diet, and chronic musculoskeletal pain remains unclear. Therefore, the purpose of this review was to systematically review the literature on the link between dietary patterns, the components of patients’ diet and chronic musculoskeletal pain. This review was conducted following the “Preferred Reporting Items for Systematic reviews and Meta-Analyses” (PRISMA) guideli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 94 publications
1
76
1
4
Order By: Relevance
“…O consumo de carboidratos acima das Recommended Dietary Allowances (RDA) (130g/ dia) (IOM, 2006) é fator agravante para o aumento de peso corporal e consequentemente de reservas adiposas, o que foi evidenciado através da avaliação antropométrica, com elevação de IMC e percentual de gordura corporal dos indivíduos avaliados. Também, o consumo excessivo de açúcares e gorduras é apontado em diversos estudos como associado à severidade da dor (RONDANELLI et al, 2018;DRAGAN et al, 2020;ELMA et al, 2020).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…O consumo de carboidratos acima das Recommended Dietary Allowances (RDA) (130g/ dia) (IOM, 2006) é fator agravante para o aumento de peso corporal e consequentemente de reservas adiposas, o que foi evidenciado através da avaliação antropométrica, com elevação de IMC e percentual de gordura corporal dos indivíduos avaliados. Também, o consumo excessivo de açúcares e gorduras é apontado em diversos estudos como associado à severidade da dor (RONDANELLI et al, 2018;DRAGAN et al, 2020;ELMA et al, 2020).…”
Section: Resultsunclassified
“…Apesar da escassez de estudos que avaliam a melhora da dor como desfecho primário para alterações na alimentação, há alguns estudos que avaliam o impacto da alimentação da modulação da dor crônica (BRAIN et al, 2018). Uma revisão sistemática e metanálise realizada por Elma et al (2020) sobre o impacto de padrões alimentares em dores musculoesqueléticas crônicas apontou ingestão excessiva de açúcares e gorduras como associada à intensidade da dor e a alimentação baseada em plantas como possivelmente relacionada à melhora da dor. Esta, assim como a dieta mediterrânea, são discutidas por serem ricas em compostos bioativos e desempenharem papel anti-inflamatório no indivíduo (RONDANELLI et al, 2018;DRAGAN et al, 2020).…”
Section: Introductionunclassified
“…As an example of its potential to assess treatment response, it has been suggested that obesity-driven inflammation in those with chronic pain may respond to nutritional interventions. 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…Besides inflammation, low dietary intake of micronutrients, especially omega-3 fatty acids, vitamins B1, B3, B6, B12 and D, magnesium, zinc and β-carotene, is also associated with chronic neuropathic or inflammatory pain [13]. Supplementation of diet with these specific nutrients contributes to alleviation of CP [29], as observed in systematic reviews on chronic pelvic pain [22], low back pain [30], rheumatoid arthritis or joint pain secondary to inflammatory bowel disease [31,32], migraine [33], chronic noncancer pain [34,35], pain in chronic liver disease [36], or aromatase inhibitor-related arthralgia in breast cancer [37].…”
Section: Introductionmentioning
confidence: 99%